The Genesis and Development of the Concept of Substance in Philosophy; from Plato to Hume - Seyyed Masoud Azarfam (Journal of Philosophical Investigations, 2023)
Substance is one of the fundamental concepts in the history of philosophy that has a history as long as the history of philosophy itself. Although this concept has underwent profound developments and assumed different layers during the centuries, because of its firm linkage with common-sense, never lost its significance. Since the birthplace of the concept of substance is ancient Greece and Greek philosophy, this essay intends to narrate an analytical history of the genesis of the concept in ancient Greece; then to trace its course of development in Christian and Islamic middle age; and finally, to investigate its remnants in modern philosophy. The purpose of this essay, however, is not merely a philosophy-historical narrative, but its secondary purpose is to place the concept of substance under a critical light and to report its fundamental critiques. Hence, we will consider the most important critiques, mostly proposed by Anglo-Saxon philosophers, and will conclude that this concept in order to have a legitimate presence in philosophy, must submit a fundamental reformulation.